The Relationship between Psychological Well Being and Quarter Life Crisis - Fauzia, Hilda; Siswanti, Dian Novita; Jafar, Eka Sufartianinsih (Polteknik Ilmu Pemasyarakatan, 2023)
Early adulthood is a phase where individuals will experience various demands and challenges from the environment. An individual's inability to overcome demands and challenges gives rise to feelings of anxiety, confusion, anxiety and an emotional crisis or quarter life crisis. The onset of a quarter life crisis is influenced by the individual's level of psychological well-being. This research aims to determine the relationship between psychological well being and quarter life crisis. The sampling technique uses non-probability sampling with the incidental sampling method. The sample in this study consisted of 450 people aged 20-29 years. Data collection was carried out using two research instruments, namely the psychological well being scale and the quarter life crisis scale. Hypothesis testing using product moment correlation analysis. The research results show that there is a significant negative relationship between psychological well being and quarter life crisis, r = -0.764 (p = 0.000). This means that the higher the psychological well-being, the lower the quarter life crisis, and vice versa. The research results also show that women have a higher quarter life crisis compared to men. Meanwhile, men's scores on psychological well-being are higher than women's. The conclusion is that early adult individuals can optimize their psychological conditions so they are able to face the quarter life crisis phase well.